Assessment of low intensivities γ-irradiation chronic influence on the state of thiol-disulphide exchange in the small intestine of rats - A. S. Anchev (Kazimierz Wielki University, 2020)
Today considerable attention is paid to the effects of ionizing radiation.chronic exposure in low doses and intensivity to humans and other bio-objects. The changes in the structural characteristics of the genome, nuclear, microsomal, mitochondrial, plasma membranes, cell proliferation, and the processes underlying radioresistance / radiosensitivity caused by irradiation have been experimentally studied. prolonged exposure to ionizing rays in small doses gradually causes a decrease in the endogenous reserve of thiol-dependent systems, and their complete depletion, which negatively affects the body's resistance to adverse environmental factors. There is a possibility of disturbances in the synthesis of  thiol disulfide high molecular weight components. The objective: to study the state of thiol disulfide, glutathione redox system and acetylcholinesterase activity in the small intestine of rats of different sexes and ages  under physiological conditions and under conditions of prolonged γ-irradiation in a total dose of 0.75 and 1.0 Gy. Results. It has been established that in a small bowel of intact mature rats after prolonged total γ-irradiation with a dose of 1.0 Gy, there were quite significant changes in the content of thiol compounds in the tissues of the small intestine. It was found that the content of SH-groups of protein origin in the tissues of the small intestine decreased relative to the age of control group animals by 28.8% and at the same time was lower than the value of males of the previous stage by 32.8%. The number of disulfide groups of protein origin in the small intestine of males three months after irradiation at a total dose of 1.0 Gy, relative to the same age control group animals, was 85.6% and at the same time was lower than the previous stage by 31.8%. Conclusions: 1.Under physiological conditions there are clear gender and age differences in the functional state of thiol-disulfide, glutathione redox system and acetylcholinesterase activity. Prolonged total γ-irradiation in the total dose of 0.75 and 1.0 Gy causes quite stable and profound changes in the functional state of the systems under study. The dependence of the detected changes on the time elapsed after radiation damage, the dose of γ-irradiation and the sex of the animals is clearly monitored. 4. Females have been shown to be more radioresistant than males.